Freedom Of Speech and Human Rights: What Can Civic Education Do? - Fatimatuz Zahrah; Siti Maizul Habibah (Jurnal HAM, 2022)
Pancasila and Citizenship Education can be considered as a way to improve citizens' opinions. This research is a critical literature review of 40 articles from 2017 to 2022 and focuses on research progress on freedom of expression. The formulation and findings of this study indicated that the practice of freedom of expression in Indonesia has been regulated by law, but in some aspects, it is subject to restrictions. People are often act uncontrollably and abuse their freedom of speech. The impact of the existence of freedom of expression is that people can express themselves but must remain in the corridor of respecting the rights of others and actively participate in providing constructive suggestions for the state. Thus, this study concludes that freedom of expression must be balanced with good delivery procedures, citizenship and civility in expressing opinions is a cultural challenge that must be resolved to build healthy freedom of speech. Citizens' civility for opinion and expression is recommended as one of the crucial issues that should be discussed and developed in Pancasila and Citizenship Education and as well as for inclusive education program.